Pengaruh Perubahan Lingkungan Usaha dan Karakteristik Kewirausahaan, Terhadap Kinerja dan Pengembangan Usaha Kecil - Itto Turyandi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2015)
The purpose of this study was to determine and assess and analyze the influence of venture capital, changes in business environment, entrepreneurial characteristics on venture performance and the impact on small business development in West Java. This study uses the approach of human resources management science are combined with theories of organizational behavior. This type of research is descriptive and explanatory verificative survey by research data cross section where the research was conducted at a specific time period with the unit of analysis is a company belonging to the small business sector across the area of ​​West Java Province, with the unit of observation is the manager or industry leaders generally doubles as a small business owner who has received Company Registration issued by the Office of Industry and Commerce of West Java Province. This study data analysis techniques using the structural equation model (structural equation model - SEM). Results of analysis of this study revealed that 1) the most dominant characteristics of entrepreneurial influence on business performance, 2) changes in business environment is a factor that most small influence on business performance; 3) intangible business capital (education, social, moral and mental) is fundamental aspects to deal with changing business environment, 4) development effort is significantly affected by the performance of the business.